Chronic histiocytic intervillositis: Outcome, associated diseases and treatment in a multicenter prospective study. (February 2015) - Mekinian, Arsène; Costedoat-Chalumeau, Nathalie; Masseau, Agathe; Botta, Angela; Chudzinski, Anastasia; Theulin, Arnaud; Emmanuelli, Virginie; Hachulla, Eric; De Carolis, Sara; Revaux, Aurélie; Nicaise, Pascale; Cornelis, Françoise; et al.
Abstract Introduction: In this prospective multicenter study, we aimed to describe (1) the outcome of pregnancy in the case of previous chronic histiocytic intervillositis (CHI), (2) the immunological findings and associated diseases, (3) the treatments, and (4) the factors associated with pregnancy loss. Methods: We prospectively included all patients with a prior CHI with ongoing pregnancy between 2011 and 2013. Results: Twenty-four women (age 34 ± 5 years) were included in this study. An autoimmune disease was present in seven (29%) cases. Twenty-one prospective pregnancies were treated. The number of live births was more frequent comparatively to the previous obstetrical issues (16/24 versus 24/76; p = 0.003). Most of the pregnancies were treated (88%), whereas only 13% of previous pregnancies were treated (p < 0.05). No difference was found with respect to the pregnancy outcome in the different treatment regimens. In univariate analyses, a prior history of intrauterine death and intrauterine growth restriction and the presence of CHI in prospective placentas were associated with failure to have a live birth. Discussion: In this multicenter study, we show the frequency of the associated autoimmune diseases in CHI, as well as the presence of autoantibodies without characterized autoimmune disease. The number of live births increased from 32% to 67% in the treated pregnancies. Despite the treatment intervention, the risk of preterm delivery remained at 30%. Last, we show that the recurrence rate of an adverse pregnancy outcome persisted at 30% despite treatment intervention. Conclusion: CHI is associated with high recurrence rate and the combined regimen seems to be necessary, in particular, in the presence of previous intrauterine death.